Sistem Informasi E-Booking Berbasis Website pada PT. SKI Land Development - Dewi, Komang Ratih Sucitya (Jurnal Informatika, 2024)
PT. SKI Land Development is a consulting service company engaged in property buying and selling consultancy services and has a standardized developer listing to avoid problematic property purchases in the future. The projects of PT. SKI Land Development are spread throughout Bali. the product marketing stage, product information, house booking, and company schedules are still done offline.. The solution provided to PT. SKI Land Development is to create a "Web-Based E-Booking Information System at PT. SKI Land Development" using HTML and PHP programming languages with the waterfall method. On the website, potential buyers can search for housing information, and the booking process can be done online. The admin can do online marketing and provide information to potential buyers through the website. While, the owner can see booking data that can be exported and printed as booking report data.The results of this application development will be tested using the black box testing method to ensure that when potential buyers, admins, and owners are using the website, it runs smoothly and is declared successful.